Teknologi Informasi Dalam Pendidikan - K Banurea, Bagus; Amalia, Isnaini; Ika Putri, Ira (Al-Ulum: Jurnal Pendidikan Islam, 2020)
Abstract: The development of technology at this time has entered the realm of the world of education, various forms of technological progress in the world of education can be accessed easily and whenever used to be used. Formerly difficult things to do now can be easily obtained, examples such as reading books, we no longer need to go to the library to buy books or buy books to be able to read books, we just open the smartphone we have and access via the internet by opening an E-book or electronic books. Not only that, the convenience provided with today's technology makes technology users spoiled, for example as we are currently being attacked by the covid-19 virus outbreak that supports us having to open the crowd for now as stated by the health protocol currently. However, with technology we can study at home and still be able to interact with friends and teachers, only with dakam, videos called online or online learning systems.Â Keywords : Education, Tecnology, Information